Chapter A case study of the PhD defence at Sofia University St Kliment Ohridski, Bulgaria - Tsvetkova, Nikolina; Stoicheva, Maria (Taylor & Francis, 2025)
This volume describes, compares, and analyses the experience of ‘defending’ the doctoral dissertation in a final oral examination in universities and traditions in the European Higher Education Area (EHEA) and beyond. Forming the basis for a comparative study of the different traditions, 11 case study chapters include analysis of the regulatory framework; semi-structured interviews with candidates, examiners, and supervisors; and ethnographic observations of the defence. Cases are drawn from universities in Bulgaria, Denmark, England, France, Germany, Italy, Portugal, Slovenia, the USA, and China. Further chapters analyse comparatively the findings in the case studies and explore crucial themes such as the nature and purpose of the defence, the composition of examining committees, the role of supervisors, and the idea of the defence as ritual and performance. Providing unprecedented levels of detail into a process often perceived as hidden from academic debate, this book will enrich the experience of both new and existing candidates as well as examiners and supervisors, and will be of further interest to researchers, scholars, and postgraduate students working on the study of higher education, international and comparative education, and assessment in higher education.